STRATEGI KEPALA SATUAN PAUD UNTUK MENINGKATKAN KOMPETENSI PROFESIONAL GURU PAUD DI KOTA BANJARMASIN - Isnaniah, Isnaniah; Maulidha, Maulidha; Nurhayati, Yuliana (EDUKIDS : Jurnal Inovasi Pendidikan Anak Usia Dini, 2025)
ABSTRACT The improvement of professional competence among early childhood education (ECE) teachers has become a strategic challenge in response to increasing demands for adaptive, reflective, and child-oriented learning quality. Field conditions indicate variations in teachers’ educational qualifications, limited supporting facilities, and suboptimal implementation of creative learning practices, highlighting the need for leadership from ECE principals who are capable of managing teacher development in a structured and sustainable manner. This study aims to describe the leadership strategies of ECE principals in enhancing teachers’ professional competence and to examine the implementation of these strategies at TK Negeri Pembina Banjarmasin Utara 3. The study employed a qualitative approach with a narrative design, involving the principal as the main subject and several teachers as supporting informants. Data were collected through in-depth interviews, observations, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings reveal that the ECE principal implemented continuous professional development through teacher learning communities, dialogical academic supervision, reinforcement of spiritual values, and participatory communication that fostered teacher collaboration. These strategies contributed to the development of reflective attitudes, increased teaching creativity, and strengthened teachers’ professional responsibility. This study concludes that participatory, humanistic, and value-based leadership of ECE principals plays a crucial role in building a sustainable culture of teacher professionalism. Peningkatan kompetensi profesional guru pendidikan anak usia dini (PAUD) menjadi tantangan strategis seiring dengan tuntutan mutu pembelajaran yang adaptif, reflektif, dan berorientasi pada perkembangan anak. Realitas di lapangan menunjukkan adanya variasi kualifikasi guru, keterbatasan sarana pendukung, serta belum optimalnya praktik pembelajaran kreatif, sehingga diperlukan kepemimpinan kepala satuan PAUD yang mampu mengelola pembinaan guru secara terarah dan berkelanjutan. Penelitian ini bertujuan untuk mendeskripsikan strategi kepemimpinan kepala satuan PAUD dalam meningkatkan kompetensi profesional guru serta menggambarkan implementasi strategi tersebut di TK Negeri Pembina Banjarmasin Utara 3. Penelitian menggunakan pendekatan kualitatif dengan desain naratif, melibatkan kepala sekolah sebagai subjek utama dan beberapa guru sebagai informan pendukung, dengan pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi, yang dianalisis melalui tahapan reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kepala satuan PAUD menerapkan pembinaan profesional secara berkelanjutan melalui komunitas belajar guru, supervisi akademik dialogis, penguatan nilai spiritual, serta komunikasi partisipatif yang mendorong kolaborasi antarguru. Strategi tersebut berkontribusi pada berkembangnya sikap reflektif, peningkatan kreativitas mengajar, dan penguatan tanggung jawab profesional guru. Penelitian ini menegaskan bahwa kepemimpinan kepala satuan PAUD yang partisipatif, humanis, dan berbasis nilai memiliki peran penting dalam membangun budaya profesionalisme guru secara berkelanjutan.